Use of odontotropic material in treatment of traumatic pulpitis in experiment - I.V. Kovach; O.V. Kopchak; E.N. Dychko; Kh.A. Buniatian; Yu.V. Khotimska; V.V. Gargin; Y.V. Lavreniuk (Medičnì Perspektivi)
The problem of diagnosis and effective treatment of one of the most common complications of dental caries, such as pulpitis, including pediatric patients, is still quite relevant at the present time. Considering anatomy-physiological and age-related features of temporary and permanent teeth in children, the rapid and aggressive course of the carious process in poorly mineralized hard tissues due to the untimely and incomplete “maturation” of them, it is beyond any doubts that scientists and practitioners involved in pediatric dentistry deal with such complications in the clinic much more often than when dealing with adults. A particularly risky group are those who develop decompensated caries, according to classification by T.F. Vinogradova. Therefore, the search for more advanced methods of diagnosis and treatment of both acute and chronic inflammation of pulp, especially with the preservation of its viability, is logical and relevant in modern dentistry. Existing methods for the biological treatment of pulpitis have their positive aspects, but possible complications up to necrosis or pulp gangrene in remote terms indicate the need for improvement both the choice of a more effective method with clear indications for its use, and the technology and material of odontotropic direction. The aim of the work was to study the results of treatment of pulpitis in experimental animals by using tricalcium silicate cement for its further application in the clinic. An experimental study was conducted on 18 animals (9-month-old male rabbits, Dutch breed) in vivarium setting to obtain information on the morphogenetic mechanisms of regeneration of living tissues and cells of dental pulp in which traumatic pulpitis was induced artificially. By the nature of odontotropic material, four groups of experimental animals were divided into: group I (control) – traumatic pulpitis was treated without special odontotropic paste, group II - treatment of pulpitis with material based on calcium hydroxide, group III - material with trioxide aggregate, group IV - material with tricalcium silicate. Every two, four, and six weeks from the moment the animals were introduced into the experiment, the damaged teeth were removed and treated in a certain way and, after special treatment, were amenable to histological examination. In the pulp tissue, the state of its main components was studied: stroma, cellular elements and blood vessels of the microvasculature. After excretion of animals from the experiment on the 2nd and 6th weeks tissues of tooth were fixed in 10% formalin. Fixed in formalin tissue has been routine proceeding after decalcification in acetic acid with making histological slides which were stained with hematoxylin and eosin (H&E), according to van Gieson, Mallory, PAS-reaction was performed.  The slides were studied with the microscope “Olympus BX-41” and followed interpretation by “Olympus DP-soft version 3.2”, which was used for morphometric study. Statistical comparison was performed using Mann-Whitney test for statistical analysis. The accepted level of significance was p<0.05. Studying the state of the pulp in the phase of acute traumatic pulpitis in dynamic observation for a month and half period, at the end of the second, fourth and sixth week the possibility of a stable restoration of the viability of the pulp as well as all its components was clearly proven. If at the beginning of a morphological study, pulp injury was accompanied by clear signs of aseptic inflammation, both cellular, vascular and stromal formations, then after a month and a half there were signs of a clear restoration of pulp viability in the biological treatment of artificial pulpitis of the second, third and fourth study groups. The most significant dynamic signs of microscopic formations of the pulp were noted in animals of the forth study group treated with odontotropic paste with tricalcium silicate. The ability of this paste to complete tissue restoration in a short time period was provn. Therefore, it should be noted that artificially induced pulpitis in experimental animals is accompanied by significant breakages in the viability of the main components of pulp tissue, such as stromal fibers, microvasculature vessels and cellular elements. Filling and odontotropic materials in pastes for capping of the damaged pulp, such as calcium hydroxide, trioxide aggregate and tricalcium silicate, have full potential for restoring the viability of injured pulp, but with varying degree of effectiveness. According to histological research, biological material with tricalcium silicate is the most effective one for restoration of the pulp in a short time period.